1991
DOI: 10.1002/app.1991.070420207
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal cation type on the structure and properties of ethylene ionomers

Abstract: SYNOPSISThermal properties by DSC, stiffness, melt viscosity, tensile properties, and dynamic mechanical properties were measured for the Na+, K', Mg2+, Zn2+, Cu2+, Mn2+, and Co2+ salts of poly (ethylene-co-methacrylic acid) (EMAA) . The changes in the structure and properties with increasing neutralization are larger in the alkaline and alkaline earth metal salts than in the transition metal salts. The stiffness shows a maximum at 33% neutralization in both the alkaline and alkaline earth metal salts, while n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
87
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 24 publications
4
87
0
Order By: Relevance
“…postulated that at higher temperatures, ionic aggregates underwent an orderdisorder transition, that is, the atomic arrangement inside the aggregates was ordered below that temperature and disordered above that temperature. This interpretation has been the subject of many papers since that time [33,34,[102][103][104][105][106][107][108][109][110][111]. EMAA or EAA copolymer ionomers have been exclusively used, and the primary evidence for this interpretation has been a DSC endothermic peak at 508C with time that grows slowly with room temperature annealing.…”
Section: Ionomer Synthesismentioning
confidence: 99%
“…postulated that at higher temperatures, ionic aggregates underwent an orderdisorder transition, that is, the atomic arrangement inside the aggregates was ordered below that temperature and disordered above that temperature. This interpretation has been the subject of many papers since that time [33,34,[102][103][104][105][106][107][108][109][110][111]. EMAA or EAA copolymer ionomers have been exclusively used, and the primary evidence for this interpretation has been a DSC endothermic peak at 508C with time that grows slowly with room temperature annealing.…”
Section: Ionomer Synthesismentioning
confidence: 99%
“…Ionomer retains pseudcross-linked structure mediated by ionic aggregates. Due to the existence of ionic aggregates, stiffness and impact resilience of EMAA ionomer are higher than those of EMAA [1][2][3][4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 97%
“…They also reported that the lowest neutralization degree for formation of ionic aggregates is 80 % for EMAA ionomer neutralized with zinc ion 2,3) . Existence is reported of ionic aggregates in EMAA ionomer at even 300 ºC which is higher than melting temperature 9) .…”
Section: Introductionmentioning
confidence: 97%
“…Kohzaki et al [6] found that the moduli of EMAA ionomers increased with aging time and ascribed it to the formation of subcrystalline ethylene in EMAA ionomers. However, Hirasawa et al [7,8] and Tadano et al [9] explained that an increase in moduli was due to the formation of ordered structure during aging process. They also reported that the order structure (ionic crystallite) did not form during the cooling process from melt, although it could form in the aging process at room temperature after the moding from melt, resulting in the increase in stiffness of EMAA ionomers.…”
Section: Introductionmentioning
confidence: 99%